Language of Mass Media: Reflection of Nowadays Myths and Ideologies - Milevich, Inga G. (Respectus Philologicus, 2003)
The article attempts an analysis of the present status of a mythological opposition our-aliens and its realization in contemporary Latvian newspaper language. The structure of this opposition is dual: on the one hand, there is an opposition we-Europe, on the other hand, opposition we-they appears. The last opposition in modern discourses first of all is realized by its invariants Russian-Latvian, citizen-non-citizen. The analysis of mythological oppositions is carried out in order to determine their pragmatic tasks and directions.